PENGELOLAAN LIMBAH MEDIS PADAT SEBAGAI UPAYA PENYEHATAN LINGKUNGAN DI RSUD BANGKINANG KABUPATEN KAMPAR - Revi Susanti; Syafruddin Nasution; Sofia Anita (Jurnal Ilmu Lingkungan, 2019)
The Purpose of this study was to analyze the types and amounts and resources of solid madical waste management including : human resources,  facilities and infrastructure as well as the costs, management status and impact of solid medical waste on the environmention Bangkinng District Hospital. This research was conducted in July – August 2019. Research subjects that made informants were the hospital director on the person in charge, head of planning, head of sanitation unit, head of friends room. Head of fighting room, head of ICU room, head of room Ali Bin Abithalib, head of IGD room, celaning service, and the people who live around Bangkinang District Hospital. This research uses survey methods with quantitaive and qualitative approach. The amount of solid medical waste generation is 30,7 kg/day and solid medical waste generated in Bangkinang District Hospital in one month was 955,7 kg. Management of solid medical waste in Bangkinang District Hospital still mixws medical waste with non mediacal waste. District hospital management of solid medical waste in Bangkinang District Hospital is not accordance with Permenkes No. 1204/MenKes/SK/X/2014, regarding hospital environmental health requirements.The impact by community around Bangkinang District Hospital is the smell smoke and shortness of breath, as well as the impact on air polution